A study on the importance of personal protective equipment (PPE) use in occupational radiation protection / Ivy June Boniface and Nur Maizatul Azra Mukhtar - Boniface, Ivy June; Mukhtar, Nur Maizatul Azra (2020)
Radiation safety and precaution become a responsibility for everyone to produce a safe radiation environment and to guarantee no human injuries and exposure occur. It should be a commonsense for every individual who works under a radiation environment to fully implement the usage of PPE to prevent the risk of being exposed accidentally to primary radiation or scattered radiation. However, it was found that there are several studies had discussed on the PPE among radiation workers happened to have lack of knowledge and awareness on the importance of PPE. Therefore, a study on the importance of PPE in occupational radiation protection is conducted by accumulating information and findings from the past study, as a systematic review. A case study was also conducted where a set of questionnaires of 29 designated question was distributed to 81 respondents working under a radiation-related environment. As a result, 82 articles were retrieved from seven databases. Of these, only 16 articles were eligible and included. From review towards radiation safety and awareness among workers, it can be seen that most of the studies have an average response with respondent not fully aware of it. In contrast, results from the case study show that the respondents were more aware of the radiation safety in their workplace with 96.3 % understands the radiation safety procedures when performing work. Furthermore, 78.3% know that there have been appropriate safety measures taken in their workplace to protect the worker from exposure. The significant percentage of 83.9% respondents are confident that the provided PPE are able to protect themselves. Therefore, awareness among workers should be emphasized more, and it is recommended that there should be more program like safety campaign and safety talk to be implemented to stress on the importance of personal protective equipment (PPE) in occupational radiation protection.